2009
DOI: 10.1111/j.1460-9568.2009.06922.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐selectivity of a thalamocortical relay neuron during Parkinson’s disease and deep brain stimulation: a computational study

Abstract: In this computational study, we investigated (i) the functional importance of correlated basal ganglia (BG) activity associated with Parkinson's disease (PD) motor symptoms by analysing the effects of globus pallidus internum (GPi) bursting frequency and synchrony on a thalamocortical (TC) relay neuron, which received GABAergic projections from this nucleus; (ii) the effects of subthalamic nucleus (STN) deep brain stimulation (DBS) on the response of the TC relay neuron to synchronized GPi oscillations; and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
1
33
1
Order By: Relevance
“…In contrast, entrainment of thalamic cells by basal ganglia input seems to be common in birds . Computational models, however, have assumed that GPi output has prominent cell-to-cell effects on thalamus, at least under parkinsonian conditions and in particular after the occurrence of bursts in GPi [Rubin and Terman, 2004, Guo et al, 2008, Guo and Rubin, 2011, Reitsma et al, 2011, Cagnan et al, 2009, Pirini et al, 2009, Meijer et al, 2011, Cleary et al, 2013. Although we found high LFP correlations between GPi and VLa, it is not clear which physiological properties are actually reflected in these correlations, and whether they describe a transmission of information.…”
Section: Gpi Vla Interneurons Vla Principal Neurons Striatumcontrasting
confidence: 53%
“…In contrast, entrainment of thalamic cells by basal ganglia input seems to be common in birds . Computational models, however, have assumed that GPi output has prominent cell-to-cell effects on thalamus, at least under parkinsonian conditions and in particular after the occurrence of bursts in GPi [Rubin and Terman, 2004, Guo et al, 2008, Guo and Rubin, 2011, Reitsma et al, 2011, Cagnan et al, 2009, Pirini et al, 2009, Meijer et al, 2011, Cleary et al, 2013. Although we found high LFP correlations between GPi and VLa, it is not clear which physiological properties are actually reflected in these correlations, and whether they describe a transmission of information.…”
Section: Gpi Vla Interneurons Vla Principal Neurons Striatumcontrasting
confidence: 53%
“…With optimized stimulation parameters, established empirically [146,177,219,220] and confirmed theoretically [38,53,137], STN-DBS is able to reduce dyskinesia and to improve motor symptoms including tremor, bradykinesia and rigidity [109,179]. However, STN-DBS is less effective for gait disturbance and postural instability, and its therapeutic benefit may decline over time [109,179].…”
Section: Introductionmentioning
confidence: 87%
“…In two recent studies we have investigated how DBS can affect the functioning of the thalamus as a relay station (Cagnan et al, 2009;Meijer et al, 2011). Although this is a simplication, it is presumed that this relay should retransmit incoming information from cortex and sensory systems back to cortex.…”
Section: Model Of the Thalamic Relay Neuronmentioning
confidence: 99%
“…Additionally we investigated the frequency dependence of this therapeutic regime and showed that in the model it persists to frequencies as low as 60 Hz, although the plateau starts at 100 Hz. In Cagnan et al (2009) we considered a similar setup but considered the frequency content of the output. In particular, we showed that DBS can diminish the power at pathological frequencies in the spectrum of the thalamic output.…”
Section: Model Of the Thalamic Relay Neuronmentioning
confidence: 99%
See 1 more Smart Citation